Meningkatkan Aktivitas Dan Hasil Belajar Menggunakan Model PBL, TS-TS DAN NHT Siswa Kelas 4 SDN Kolam Makmur - Maya Nurhaliza; Mahmuddin (CV. ITTC INDONESIA, 2023)
The issue in this study is the low activity and student learning results. To construct development and learning results experts use the Issue Based Learning (PBL) learning model got together with Two Stay Two Wanderer (TS) and Number Head Together (NHT). The inspiration driving this study is to depict teacher practices and analyze student activities and learning results. This survey uses an emotional and quantitative assessment approach with the kind of Study corridor Action Investigation (PTK) which is finished in 2 cycles with 3 social occasions. The subjects of this review were the fourth grade understudies of SDN Kolam Makmur Barito Kuala, adding up to 26 understudies comprising of 17 male understudies and 9 female understudies. The consequences of the review showed that educator action in cycle I meeting 1 got a score of 25 (78%) with the